2019
DOI: 10.1038/s41598-019-49863-x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural responses of the hagfish Eptatretus stoutii to nutrient and noxious stimuli

Abstract: The suitability of a traditional testing paradigm (e.g. choice chamber) for assessing chemosensory behaviour in the Pacific hagfish, Eptatretus stoutii, was examined. Actively-swimming hagfish, tested at night, showed no preference for any region of a T-maze in the absence of a stimulus, but in the presence of an olfactory food cue, spent significantly more time in the zone where the cue was placed. Conversely, hagfish avoided spending time in the zone the fish anaesthetic 3-amino benzoic acid ethylester (MS-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Still, the hagfish appears to have an advantage in behavioral experiments over the lamprey because it will feed in an aquarium. Recently, Glover et al (2019) reported that the chemosensory behavior of the hagfish can be assessed using a modified T-maze arena, in which food or noxious stimuli are placed in one of the arms of the maze. This suggests that hagfish learning behavior can be investigated using food as a reward.…”
Section: Hagfishmentioning
confidence: 99%
“…Still, the hagfish appears to have an advantage in behavioral experiments over the lamprey because it will feed in an aquarium. Recently, Glover et al (2019) reported that the chemosensory behavior of the hagfish can be assessed using a modified T-maze arena, in which food or noxious stimuli are placed in one of the arms of the maze. This suggests that hagfish learning behavior can be investigated using food as a reward.…”
Section: Hagfishmentioning
confidence: 99%
“…Adult sea lamprey uses odours from conspecific larvae (including dihydroxylated tetrahydrofuran fatty acids and some bile acids) to select the best streams for spawning based on their larval population [55][56][57][58][59]. Hagfishes are usually found in deep water and their olfactory organ seems particularly efficient as they have been shown to be among the first fish species to locate chemical signals of decaying prey [60,61]. Electrophysiological recordings indicate that their olfactory sensory neurons are particularly sensitive to amino acids [62].…”
Section: The Olfactory System In Jawless Vertebratesmentioning
confidence: 99%